2008
DOI: 10.1002/anie.200803326
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Intramolecular Oxa‐Michael Addition of Activated α,β‐Unsaturated Ketones Catalyzed by a Chiral N,N′‐Dioxide Nickel(II) Complex: Highly Enantioselective Synthesis of Flavanones

Abstract: The title reaction provides a promising approach for the synthesis of chiral flavanones with broad substrate scope and is tolerant to air and moisture. Good to excellent enantioselectivities and high yields were achieved for most substrates under mild conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
31
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(31 citation statements)
references
References 71 publications
0
31
0
Order By: Relevance
“…The key step in the strategy is the application of our asymmetric thiourea-catalyzed cyclization, which can provide controlled access to either stereoisomer of these natural products 7,17. A Knoevenagel condensation between an appropriately protected β-keto ester and different aldehydes corresponding to each abyssinone would provide the requisite alkylidenes for our thiourea-catalyzed cyclization.…”
mentioning
confidence: 99%
“…The key step in the strategy is the application of our asymmetric thiourea-catalyzed cyclization, which can provide controlled access to either stereoisomer of these natural products 7,17. A Knoevenagel condensation between an appropriately protected β-keto ester and different aldehydes corresponding to each abyssinone would provide the requisite alkylidenes for our thiourea-catalyzed cyclization.…”
mentioning
confidence: 99%
“…All the above methods give racemic mixtures. Yet, only a few stereoselective methods have been developed for generating enantio‐enriched flavanoids via carbon‐carbon and carbon‐heteroatom bond formation,.Recently, biologically interesting asymmetric flavanones have been synthesized using activated alkylidene β ‐ketoesters via a catalytic asymmetric intramolecular oxa‐Michael reaction by using chiral N, N’‐Dioxide Nickel(II) Complex . Scheidt and co‐workers used asymmetric cinchona derived thiourea organocatalyst for cyclization of activated 2‐hydroxy alkylidene β‐ketoesters .…”
Section: Figurementioning
confidence: 99%
“…Literature survey revealed that tert ‐butyl ester functional group of the chalcone substrate enhances the reactivity of conjugate acceptor, thus playing a crucial role in the cyclization reactions ,. It also provides a subsequent basic position for potential interaction with catalyst which acts as bifunctional (Scheme ).…”
Section: Figurementioning
confidence: 99%
“…Asymmetric catalysis for intramolecular conjugate addition of 2′-hydroxychalcones such as our HWE enone product 31 (R 1 ≠ R 2 ) could therefore represent a potentially convenient means of accessing 2,2-disubstituted chiral chromanones using a variety of organocatalysts (Scheme 10). [41][42][43][44][45][46] Future work aims to explore this avenue of investigation.…”
Section: Completion Of the Synthesis Of Gonytolide C (2a)mentioning
confidence: 99%